Numerical investigation on the effect of building overhang on the flow within idealised two-dimensional street canyon / Muhammad Fatih Ibrahim …[et al.] - Ibrahim, Muhammad Fatih; Mohamad, Mohd Faizal; Ikegaya, Naoki; Abd Razak, Azli (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Building overhang is an essential element in the construction of terrace houses in Malaysia to protect occupants from the sunlight, car parking, and social event purposes. However, there is still a lack of study investigating the effect of overhang in a windy area of terrace houses despite its effect on the flow modification around the building. Therefore, in this paper, a series of computational fluid dynamics (CFD) simulations were performed using Reynolds Average Navier Stokes(RANS) equations and renormalization group (RNG) k – ε as the turbulence closure model. Simulations were conducted on a unity aspect ratio of two-dimensional street canyon representing the low-rise terrace house area in a flat roof shape and three different overhang conditions. The protruding overhangs were significantly modified the in-canyon flow structure as it limited the penetration of the above flow into the canyon as compared to the without overhang case. In addition, spatially-averaged ? of the turbulent kinetic energy depicted that the value decreased within the canyon, demonstrating the independence of the overhang location. It is recommended to perform a further study on the ventilation performance of the street canyon through evaluation of ventilation indices such as ventilation rate, air exchange rate (ACH), and pollutant exchange rate (PCH).